2013
DOI: 10.1002/jmv.23554
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory/regulatory cytokine microenvironment mediated by IL‐4 and IL‐10 coordinates the immune response in hemophilia A patients infected chronically with Hepatitis C virus

Abstract: In the past decades patients with hemophilia were infected commonly by hepatitis C virus (HCV) and a significant number of patients are infected chronically. Focusing on the role of the immune system for controlling and or maintaining HCV infection, the leukocyte and cytokine profiles of peripheral blood from hemophilia A patients and other patients with and without HCV infection were studied. The results demonstrated that hemophilia A is characterized by a general state of circulating leukocytes activation al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…In addition, lipid levels, which are a component of many CVD risk stratification tools are known to be decreased in CHC patients, 173 45 Antonelli et al 51 Caliskan et al 55 Cielecka-Kuszyk et al 56 Falasca et al 164 Siloşi et al 166 Ramos-Casals et al 167 Riccio et al 169 Nascimento et al 162 45 Caliskan et al 55 Cielecka-Kuszyk et al 56 Mezher et al 68 Elsammak et al 74 Pawlak et al 160 Siloşi et al 166 Ramos-Casals et al 167 Antonelli et al 168 sTNFRI/II el-Din et al 165 Realdon et al 170 CRP/hsCRP Caliskan et al 55 Yelken et al 158 Chennu et al 159 Pawlak et al 160 Caliskan et al 161 Nascimento et al 162 HCV-infected and HCV uninfected patients, 100,174 and there is a growing concern that CVD risk assessment using current risk scoring tools may be suboptimal for patients with heightened inflammatory states leading to an underestimation of risk in these patients. 175 CRP is an established cardiac biomarker for increased CVD risk and has been included in traditional risk assessment algorithms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, lipid levels, which are a component of many CVD risk stratification tools are known to be decreased in CHC patients, 173 45 Antonelli et al 51 Caliskan et al 55 Cielecka-Kuszyk et al 56 Falasca et al 164 Siloşi et al 166 Ramos-Casals et al 167 Riccio et al 169 Nascimento et al 162 45 Caliskan et al 55 Cielecka-Kuszyk et al 56 Mezher et al 68 Elsammak et al 74 Pawlak et al 160 Siloşi et al 166 Ramos-Casals et al 167 Antonelli et al 168 sTNFRI/II el-Din et al 165 Realdon et al 170 CRP/hsCRP Caliskan et al 55 Yelken et al 158 Chennu et al 159 Pawlak et al 160 Caliskan et al 161 Nascimento et al 162 HCV-infected and HCV uninfected patients, 100,174 and there is a growing concern that CVD risk assessment using current risk scoring tools may be suboptimal for patients with heightened inflammatory states leading to an underestimation of risk in these patients. 175 CRP is an established cardiac biomarker for increased CVD risk and has been included in traditional risk assessment algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…The immune activation associated with CHC infection can lead to the development of immune related complications, which may further influence the levels of inflammatory markers associated with CVD. Increased levels of IL‐6, IL‐10, TNF‐α, and sTNFR in HCV‐infected patients with complications such as cryoglobulinemia, Sjogren syndrome, lymphoproliferative diseases, hemophilia, and HCV related arthritis have been reported compared to CHC‐infected patients without such complications or to healthy controls …”
Section: Special Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We had hypothesized that intrinsic downregulation of the immune system (decreased IL8 and IL12) in the hemophilic population infected with HCV and repeated exposure to blood products with various HCV sub-species would result in increased accumulation and prevalence of naturally occurring mutations. 7,23 However, it has been shown that PI-resistant HCV mutants have reduced fitness as a consequence of impaired production of infectious virions, and the continuous process of selection for variants with the greatest fitness may extinguish the presence of minor species. 24 We did note a trend towards an increase (3.8 fold) in dominant mutation numbers in coinfected hemophiliacs compared to coinfected controls, suggesting decreased immune clearance in hemophiliacs with HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Th1 mediated activation involves secretion of interferon gamma (INFG), tumor necrosis factor alpha (TNFA) and IL-1, while that of Th2 includes IL-4, IL-5, IL-6 and IL-10 [32]. Hemophilia A patients are generally characterized by an overall increase in the frequency of IL-6 and IL-10 with decrease of IL-8 and IL-12 [33]. In a previous study by Hu G et al (2007), FVIII exposure was reported to significantly increase IFNG-producing CD4(?)…”
Section: Hla and Immune Related Genes In Inhibitor Productionmentioning
confidence: 99%